Experimentally decomposing phytoplankton community change into ecological and evolutionary contributions. (8th November 2021) - Hattich, Giannina S. I.; Listmann, Luisa; Govaert, Lynn; Pansch, Christian; Reusch, Thorsten B. H.; Matthiessen, Birte
Abstract: Shifts in microbial communities and their functioning in response to environmental change result from contemporary interspecific and intraspecific diversity changes. Interspecific changes are driven by ecological shifts in species composition, while intraspecific changes are here assumed to be dominated by evolutionary shifts in genotype frequency. Quantifying the relative contributions of interspecific and intraspecific diversity shifts to community change thus addresses the essential, yet understudied question as to how important ecological and evolutionary contributions are to total community changes. This debate is to date practically constrained by (a) a lack of studies integrating across organizational levels and (b) a mismatch between data requirements of existing partitioning metrics and the feasibility to collect such data, especially in microscopic organisms like phytoplankton. We experimentally assessed the relative ecological and evolutionary contributions to total phytoplankton community changes using a new design and validated its functionality by comparisons to established partitioning metrics. We used a community of coexisting Emiliania huxleyi and Chaetoceros affinis with initially nine genotypes each. First, we exposed the community to elevated CO2 concentration for 80 days (~50 generations) to induce interspecific and intraspecific diversity changes and a total abundance change. Second, we independently manipulated the induced interspecific and intraspecific diversity changes in an assay to quantify the corresponding ecological and evolutionary contributions to the total change. Third, we applied existing partitioning metrics to our experimental data and compared the outcomes. Total phytoplankton abundance declined to one‐fifth in the high CO2 exposed community compared to ambient conditions. Consistently across all applied partitioning metrics, the abundance decline could predominantly be explained by ecological shifts and to a low extent by evolutionary changes. We discuss potential consequences of the observed community changes on ecosystem functioning. Furthermore, we explain that the low evolutionary contributions likely resulted of intraspecific diversity changes that occurred irrespectively of CO2 . We discuss how the assay could be upscaled to more realistic settings, including more species and drivers. Overall, the presented calculations of eco‐evolutionary contributions to phytoplankton community changes constitute another important step towards understanding future phytoplankton shifts, and eco‐evolutionary dynamics in general. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.